High on Cannabis and Calcineurin Inhibitors: A Word of Warning in an Era of Legalized Marijuana - Naomi Hauser; Tanmay Sahai; Rocco Richards; Todd Roberts (Case Reports in Transplantation)
Tacrolimus, a potent immunosuppressant medication, acts by inhibiting calcineurin, which eventually leads to inhibition of T-cell activation. The drug is commonly used to prevent graft rejection in solid organ transplant and graft-versus-host disease in hematopoietic stem cell transplant patients. Tacrolimus has a narrow therapeutic index with variable oral bioavailability and metabolism via cytochrome P-450 3A enzyme. Toxicity can occur from overdosing or from drug-drug interactions with the simultaneous administration of cytochrome P-450 3A inhibitors and possibly P-glycoprotein inhibitors. Tacrolimus toxicity can be severe and may include multiorgan damage. We present a case of suspected tacrolimus toxicity in a postallogeneic hematopoietic stem cell transplant patient who was concurrently using oral marijuana. This case represents an important and growing clinical scenario with the increasing legalization and use of marijuana throughout the United States.